Effects of circular oscillating beam on heat transfer and melt flow of laser melting pool - Chen Zhang; Xinwei Li; Ming Gao (Journal of Materials Research and Technology, 2020)
Circular oscillating laser welding can improve welding quality, but its thermodynamics of the melt pool is not clear. In this study, the basic mechanism during circular oscillating laser welding process was studied by computational fluid dynamics method. The calculation model was verified by experimental results. The results show that the circular oscillating laser reduced the peak temperature and temperature gradient and formed a new vortex in the melt pool. The ascending oscillation frequency and amplitude reduced the temperature gradient and increased the velocity of melt flow significantly. Related mechanisms were revealed at the end. This study proves that circular oscillating laser provides a new way to optimize the laser melting process and have great application values for welding and additive manufactering.